Determinants of inflation in upper-middle income countries / Nur Syahiratasha Hamdan - Hamdan, Nur Syahiratasha (2018)
This research paper focus on the analysis of the main determinants that may have an impact on inflation. Precisely, this study aims to determine the main determinants of inflation in upper-middle income countries by analyzing the relationship of GDP growth, exchange rate growth, real interest rate and money and quasi money growth with the inflation. This study using a sample of 15 upper-middle income countries over the 1998 to 2007 period. All the data that have been collected from World Bank and Econ Stats will be regressed by using E-views 10. These findings suggest that GDP growth, exchange rate growth and real interest rate gives significant negative signs meanwhile money and quasi money growth gives significant positive signs towards the inflation rate in upper-middle income countries.